Penerapan Model Problem Based Learning (PBL) Di Sekolah Dasar - Afni, Nur (Universitas Sebelas Maret, 2020)
Education in elementary schools is the initial foundation for students to get education in the next stage. The results of the education process in junior and senior high school are much dependent on how learning in elementary schools is designed by teachers. Therefore, it is important for teachers to apply appropriate learning models that match to the characteristics of the students and able to improve the students' thinking skills. Many learning methods or models have been used by teachers, especially those teaching in elemenatry schools to improve the students' higher order thinking (HOTS) skill. One of the learning models applied is the Problem Based Learning (PBL). Through this model, the students will be exposed to the real problem, and in groups they will analyze why the problem occurs, what factors trigger its occurence, and how to solve the problem. This model is expected to improve the students‘ high-level thinking skill and initiate collaboration that are certainly adjusted to the capability of elementary school students.